Pemanfaatan Ekstrak Kitosan dari Limbah Sisik Ikan Bandeng di Selat Makassar pada Pembuatan Bioplastik Ramah Lingkungan - Muhammad Fikri Bill Gufran; Nasruddin Aziz; William Pitoyo; Suhandi Suhandi (Hasanuddin Student Journal, 2017)
Makassar Strait as an area of marine waters located on the west coast of South Sulawesi that has the potential of milkfish resources with considerable production. The production of milkfish is quite high and almost covers all provinces in Indonesia. Total milkfish production in 2014 reached 631,125 tons Or 14.74 percent of the total production of aquaculture fish. Its large potential is directly proportional to the quantity of waste- fish scales produced. Utilization of chitosan in waste- fish scales become bioplastics for the manufacture of environmentally friendly disposable cutlery is expected to be a smart solution in an effort to reduce the impact of contamination of waste- fish scales. Chitin content on the scales is isolated by demineralization and deproteination treatment. This study used waste scales from milkfish (Chanoschanos). Chitin is then produced through deacetylation treatment to produce chitosan compounds. A number of chitosan are dissolved in acetic acid then mixed with sorbitol to produce a bioplastics solution which can then be molded and dried to produce bioplastics. This study varied between commercial chitosan and chitosan fish scales with a certain ratio.Keywords: Bioplastics, Milkfish, Chitosan